SARS-CoV-2 virus-like-particles via liposomal reconstitution of spike glycoproteins - McColman, Sarah; Shkalla, Klaidi; Sidhu, Pavleen; Liang, Jady; Osman, Selena; Kovacs, Norbert; Bokhari, Zainab; Forjaz Marques, Ana Carolina [UNESP]; Li, Yuchong; Lin, Qiwen; Zhang, Haibo; Cramb, David T. (Royal Society of Chemistry (RSC), 2023)
The SARS-CoV-2 virus, implicated in the COVID-19 pandemic, recognizes and binds host cells using its spike glycoprotein through an angiotensin converting enzyme 2 (ACE-2) receptor-mediated pathway. Recent research suggests that spatial distributions of the spike protein may influence viral interactions with target cells and immune systems. The goal of this study has been to develop a liposome-based virus-like particle (VLP) by reconstituting the SARS-CoV-2 spike glycoprotein within a synthetic nanoparticle membrane, aiming to eventually establish tunability in spike protein presentation on the nanoparticle surface. Here we report on first steps to this goal, wherein liposomal SARS-CoV-2 VLPs were successfully produced via detergent mediated spike protein reconstitution. The resultant VLPs are shown to successfully co-localize in vitro with the ACE-2 receptor on lung epithelial cell surfaces, followed by internalization into these cells. These VLPs are the first step toward the overall goal of this research which is to form an understanding of the relationship between spike protein surface density and cell-level immune response, eventually toward creating better vaccines and anti-viral therapeutics.